Personal income tax design and background-related earnings advantages: evidence from Italy and Poland. Issue 8 (12th May 2021) - Bloise, Francesco; Franzini, Maurizio; Raitano, Michele
Abstract : Purpose: The authors analyse how the association between parental background and adult children's earnings changes when net rather than gross children's earnings are considered and disentangle what such changes depend on: differences between pre and after taxes earnings inequality or reranking of individuals along the earnings distribution before and after taxes. Design/methodology/approach: Using data from European Union Statistics on Income and Living Conditions (EU-SILC) 2011, the authors focus on two large European countries, Italy and Poland, with comparable levels of inequality and background-related earnings premia but very different personal income tax (PIT) design and estimate – at both the mean and the deciles of the earnings distribution – the association between parents' characteristics and children's gross and net earnings. Findings: The authors find that in Italy the PIT reduces the magnitude of the association between parental background and adult children's earnings at the top of the distribution, while no effects emerge for Poland, and the reduction is mostly due to a decrease in earnings inequality rather than to a re-ranking of children along the distribution. The findings are confirmed when the authors simulate the introduction of a "quasi flat tax" regime in Italy. Social implications: The findings suggest that the higher the tax progressivity, the higher the background-related inequality reduction and the lower the intergenerational association, signalling that the degree of progressivity amongst children may be an effective weapon to reduce intergenerational inequality. Originality/value: In the literature on intergenerational inequality, the role of taxes is usually overlooked. In this paper, the authors try to fill this gap and enquire how the PIT design affects the association between parental background and adult children's earnings.